Information Externalities of SFAS 161: Evidence from Supply Chains - Chen, Jing; Dou, Yiwei; Zou, Youli (The Accounting Review, 2021)
ABSTRACT Effective in 2009, SFAS 161 requires enhanced disclosures about derivative use and hedging activities. We test for changes to the information environment of firms whose disclosure policy is unaffected by this standard directly. Using a sample of non-users of derivatives, we find an increase in stock liquidity after their critical customers expand derivative disclosures under SFAS 161. The effect persists for one year and becomes insignificant in subsequent years as the firms dial back their voluntary disclosure. The effect is also more salient for firms that have stronger economic links with their customers and for firms whose customers exhibit more significant improvements in derivative disclosures. The findings suggest that the mandatory derivative disclosures due to SFAS 161 lead to short-term positive information externalities along supply chains. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: G32; M41; M48.